Christian Mission In The Twentieth Century - Yates, T. E. (Timothy Edward) (Cambridge [England] ; New York Cambridge University Press, 1994)
This widely acclaimed book gives historical focus and perspective to developments in Christian mission this century. The author concentrates on the leading figures of each decade, beginning with events leading up to the 1910 Edinburgh Conference and inclu
Keywords: Missions -- Theory -- History of doctrines -- 20th century. Missions -- Theory -- History of doctrines. Zending